Upregulation of β3-Adrenergic Receptor Expression in the Atrium of Rats With Chronic Heart Failure. (March 2013) - Zhao, Qiang; Zeng, Fang; Liu, Jiang-Bo; He, Yun; Li, Biao; Jiang, Zuo-Feng; Wu, Tong-Guo; Wang, Le-Xin
Objectives: To investigate the expression of β3 -adrenergic receptor (β3 -AR) in the atrium of rats with chronic heart failure (CHF). Methods: The heart failure rat model was established by aortic constriction. Thirty-six male Wistar rats were divided into Sham group (n = 10) and heart failure model group (n = 26), which were further divided into CHF control (CHF group) and BRL group. The rats in the BRL group were treated with a selective β3 -AR agonist, BRL-37344 (4.0 nmol/kg, twice weekly) for 4 weeks. Results: In the BRL group, the left ventricular end-systolic pressure (83.21 ± 13.0 vs 101.50 ± 12.12 mm Hg) and the absolute values of the maximal rate of rise and fall of left ventricular pressure ([±dP/dtmax] 2.81 ± 0.04 vs 0.35 ± 0.04 and −2.72 ± 0.06 vs −3.33 ± 0.06) were lower than in the CHF group ( P < .01). The left atrial mass index (LAMI) in the BRL group (0.4132 ± 0.0306) was higher than that in the CHF (0.3212 ± 0.0136) or Sham group (0.2683 ± 0.0145; P < .01). The levels of the left atrial β3 -AR messenger RNA (mRNA) expression in the BRL group (0.932 ± 0.055) was higher than that in the CHF (0.706 ± 0.043) or Sham group (0.310 ± 0.020; P < .01). In all animals, there was a positive correlation between the level of β3 -AR mRNA expression and the left or right atrial mass index (correlation coefficient ranged from 0.744 to 0.937). Conclusion: There is a significant increase in the β3 -AR mRNA expression in the atrium of rats with heart failure. The level of β3 -AR mRNA expression was associated with the AMI and was enhanced by a selective β3 -AR agonist, BRL-37344.